“Although The Loneliness is Great, Greater Yet is the Love of my Country”: Archaeology of a Military Outpost on the Topaín Hillock (Antofagasta Region, Chile) - Prieto, Manuel; Vila, Xurxo M. Ayán (Journal of Contemporary Archaeology, 2015)
Since the War of the Pacific against Peru and Bolivia (1879 1883), the Chilean State has constantly reproduced its sovereign power in the Atacama Desert by using different technologies of governance. During the Pinochet military regime (1973–1990), this process was radicalized through the militarization of the area. This militarization, in turn, produced new materialities in the desert landscape, such as the Topaín military outpost. In this article, we use archaeological evidence in order to reveal the everyday life of this base. This research is the first approach to this geographic area from the perspective of the Archaeology of Conflict. This, in turn, constitutes a methodological innovation for developing a new understanding of the reproduction of contemporary state sovereignty through the material culture of everyday life.